Avaliação da efetividade do sistema de captação de água da chuva para fins não potáveis na Universidade Federal do Pampa Campus Alegrete – Alegrete (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present work was elaborated with the purpose of evaluating technically the effectiveness of rainwater harvesting system of the Federal University of Pampa - Alegrete Campus. Water is a necessary commodity for everyone and is currently in focus because its waste and misuse made it scarce. In order to carry out this work, it was necessary to know the existing facilities in the academic – 1 and 2 – and administrative buildings. Through the technical evaluation it was possible to determine that the current installation of the reservoirs is of adequate size. However, it only serves Academic Building 2, does not have enough catchment area and the height of the drinking water intake regulator float is not in the most adequate position, making the system not work efficiently. Improvements were proposed in the system and after daily simulations increasing the catchment area of the system it was possible to verify that the guarantee of service can reach up to 67% of the demand for non-potable water used in sanitary vessels supplying the three buildings. The university currently spends 220 m³ of drinking water per month, which confirms that the implementation and adequacy of the proposed system would generate financial savings in addition to contributing to the better use of water resources, avoiding waste and consequently generating a more sustainable consumption.
Keywords: Engenharia civil; Água pluvial; Água não potável; Universidade; Civil Engineering; Rainwater; Non-potable water; University; CNPQ::ENGENHARIAS